THE ISSUE OF UNCLAIMED PROPERTY IN STATE OF SELANGOR - Muhammad Azwan Sulaiman; Hadirah Afiqah Hamidon; Nor Nadirah Akmar Mokhtar; Nurul Nadiah Zainol; Mohamad Isa Abdullah (Journal of Islamic, Social, Economics and Development, 2022)
In this research, the issue of unclaimed property in Selangor is being discussed.Unclaimed property has been identified as a significant issue by Malaysian researchers. Wealthcannot be utilized, which is detrimental to the Malaysian economy. It continues to grow yearafter year, with no end in sight. This research aims to uncover the causes that contribute toestate distribution delay, determine the implications, and identify the legislation issue on theseongoing problems. Unclaimed property is on the rise due to a few circumstances, includinglack of public awareness, social and economic concerns, and administrative and legal issues.People educated about property administration will be less likely to inherit a frozen inheritance.The researchers adopted a qualitative technique, asking a series of open-ended questionsduring a semi-structured interview between December 2021 and January 2022. As therespondents have a general understanding of Islamic estate management and inheritance, amodest sample size is sufficient, and the researchers used judgmental sampling. To identify thecode and themes, the researchers employed thematic analysis. As a result, this researchprovides an overview of the issues and solutions to lowering the rise in unclaimed property.